LeiKA: an optional German general practice teaching project for first-semester medical students: who is taking part and why? A cross-sectional study. Issue 10 (31st October 2019) - Geier, Anne-Kathrin; Saur, Christiane; Lippmann, Stefan; Nafziger, Melanie; Frese, T; Deutsch, Tobias
Abstract : Objectives: This study investigates students' adoption of LeiKA, a new extracurricular longitudinal general practice (GP) teaching project. LeiKA aims to attract a broad range of students, not only those who are already planning to become GPs. This study compares participants' and non-participants' characteristics, career preferences and job-related value orientations to assess the programme's initial potential to increase the number of students subsequently entering GP careers. Additionally, students' motives for taking part in the programme were explored. Design: We analysed administrative data and data from a cross-sectional questionnaire survey for the first three cohorts. LeiKA participants were compared with non-participants regarding baseline characteristics, career intentions and attitudes associated with GP careers. There was also a qualitative analysis of the reasons for taking part. Setting: Faculty of Medicine, University of Leipzig, Germany. Participants: First-semester medical students in the years 2016–2018. Results: In the first 3 years, 86 of 90 LeiKA slots were taken, 9.0% (n=86/960) of those eligible to apply. LeiKA participants were a mean of 0.6 years older (LeiKA: 21.5 vs whole cohort: 20.9 years, p<0.001) and slightly more interested in long-term doctor–patient relationships (3.6 vs 3.3, scale from 1 'unimportant' to 5 'very important', p=0.018), but did not differ regarding other characteristics and attitudes. Although more participants definitely favoured a GP career (13.1% vs 4.9%, p=0.001), it was a possible option for most students in both groups (78.6% vs 74.0%). Early acquisition of skills and patient contact were the main motives for taking part, stated by 60.7% and 41.7% of the participants, respectively. Conclusions: The extracurricular programme was taken up by a broad range of students, indicating its potential to attract more students to become GPs. The reasons for taking part that we identified may guide the planning of other similar projects.